2018
DOI: 10.1108/ijbpa-06-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Factors for the adoption of green building specifications in China

Abstract: Purpose-Green building specifications, areas some of the most important strategies for energy saving, and describe the best practice in the field of sustainable construction. They have great effects on resource saving and environmental protection. The demand of sustainable construction has spurred the emerging and development of green building specifications. However, there are many factors that affect the adoption of green building specifications in China. Therefore, the purpose of this paper is to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
0
24
1
2
Order By: Relevance
“…This was supported by Darko et al (2017) who have done similar research and found out that this factor is the highest ranked barrier to green building adoption in United States. However, this result was contrast with another similar study by Wang et al (2018a), who claiming that this factor was the lowest ranked influential factor of the adoption of green building specifications in China. Thus, it could be inferred that the significance of this factor was varied in accordance to different geographical locations the study conducted.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…This was supported by Darko et al (2017) who have done similar research and found out that this factor is the highest ranked barrier to green building adoption in United States. However, this result was contrast with another similar study by Wang et al (2018a), who claiming that this factor was the lowest ranked influential factor of the adoption of green building specifications in China. Thus, it could be inferred that the significance of this factor was varied in accordance to different geographical locations the study conducted.…”
Section: Discussioncontrasting
confidence: 98%
“…There are several statistics indicating the massive consumption or usage of resources in other countries due to development of construction industry. In China, Wang et al (2018a) stated that forty percent steel and cement in the world, amounted to 2 billion m 3 will be used by new buildings. They also stated that China is the second largest building energy user in the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most interesting goal for the construction industry is the goal of sustainable development of cities and settlements, to achieve which there is already a good reserve, for example, scientists around the world have done a lot of research works in the field of energy and resource conservation. That fact is confirmed by a lot of publications in different countries [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 55%